Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357077
|View full text |Cite
|
Sign up to set email alerts
|

Precision timing in human-robot interaction

Abstract: As research over the last several decades has shown that non-verbal actions such as face and head movement play a crucial role in human interaction, such resources are also likely to play an important role in human-robot interaction. In developing a robotic system that employs embodied resources such as face and head movement, we cannot simply program the robot to move at random but rather we need to consider the ways these actions may be timed to specific points in the talk. This paper discusses our work in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In humans, the study of synchronization skills has fundamental applications in the early diagnosis of social disorders as autism (Delaherche et al, 2013). Regarding synchrony and temporization, Yamazaki et al (2008) analyzed human–human interaction to highlight some transition relevant places (TRPs) corresponding to the moments when a speaker's turn is about to end. Emphasized keywords, unfamiliar and deictic words are other examples of focus points.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the study of synchronization skills has fundamental applications in the early diagnosis of social disorders as autism (Delaherche et al, 2013). Regarding synchrony and temporization, Yamazaki et al (2008) analyzed human–human interaction to highlight some transition relevant places (TRPs) corresponding to the moments when a speaker's turn is about to end. Emphasized keywords, unfamiliar and deictic words are other examples of focus points.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies we know that the perception of eye contact with Nao as a looker, is very similar compared to a human looker [43]. Also, several studies have shown that looking back at the participant is interpreted as a turn-taking cue for various agents [44][45][46] including the Nao robot [34,47,48]. In Fig.…”
Section: Gaze: the Head Movementmentioning
confidence: 92%
“…Yamazaki et al . examined how human participants respond nonverbally to a robot when the robot's head turns and gaze are coordinated to its vocal utterances at transition‐relevant instances . Moreover, Yamazaki et al .…”
Section: Related Workmentioning
confidence: 99%